A sketch of youth unemployment in selected countries - Johanna Alatalo; Jorunn Furuberg; Håkan Gustavsson; Kristian Krüger Henriksen; Sabine Klinger; Anne Lauringson; Johannes Sørbø; Kristi Villsaar (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Since the great recession in 2008, unemployment has risen in the EU. In 2008, the unemployment in the EU was at 7.1 percent, in 2012 it was at 10.5 percent. The unemployment has increased the most in southern Europe, while Germany today has a lower unemployment than in 2008. By the end of 2012, the euro area was still in recession, and unemployment continues to rise. Young people are especially sensitive to the business cycles, and youth unemployment (15-24 years) has increased from 15.8 percent in 2008 to 22.8 percent in 2012 in the EU. The situation is worst in Greece and Spain with youth unemployment above 50 percent. In this paper the authors of the International Labour Market Forecasting Network (a cooperation of several researchers related to PES) briefly describe the youth unemployment in Denmark, Estonia, Finland, Germany, Norway and Sweden. Young people face the transition from education to work, which is a vulnerable phase. If the labour market is poor, they struggle to get their first job. If firms have to resign workers they often will be the first to go, because they have temporary contracts and/or short experience. This means that youth unemployment usually is higher than unemployment for people older than 24 years. In the countries named above youth unemployment is about 2-4 times higher than total unemployment (LFS), but most of the young who are unemployed are only unemployed for a short period of time. In some of the countries many of the young unemployed are full-time students looking for a part-time job. In all countries except Germany the youth unemployment is higher than 2008, but since 2010 youth unemployment has stabilized or fallen in most of the countries according to the labour force survey (LFS).
Keywords: 330